MODIFICATION "OF RTV SILICONE - Ramadan, N A; Saleh, A M M; Fouad, M M K (Biological Sciences - PJSIR, 2002)
Owing to their broad spectrum of properties, silicone sealants are used in a large variety of purposes in Egypt. However, among the drawbacks of their use are low abrasion resistance, low tensile properties and high cost owing to the fact that they are completely imported. In the presented research, silicone sealants [Room Temperature Vulcanized (RTV)] have been formulated using local expertise and raw material (silicone polymer, ethyl silicate and dibutyl tin diacetate). In addition, two types of asphalt locally produced in Egypt (asphalt cement of penetration grade 60/70 and blown asphalt of type 115/15) as well as asbestos, fumed silica and reclaimed rubber have been used to produce modified silicone sealants thereby overcoming their high cost and producing high quality local cheap sealants. Results show the wide range of mechanical properties and chemical resistivities of the produced products.